Phanerochaete chrysosporium-driven quinone redox cycling promotes degradation of imidacloprid. (July 2020) - Xie, Qingru; Xue, Chao; Chen, Anwei; Shang, Cui; Luo, Si
Abstract: This study systematically investigated the advanced oxidation processes driven by the white-rot fungus (WRF) Phanerochaete chrysosporium in the removal of the neonicotinoid pesticide imidacloprid (IMI). The quinone redox cycling driven by P. chrysosporium promotes the degradation of IMI in presence of Mn 2+ and Fe (III)-oxalate. Results showed that the degradation efficiency varied with the type of quinine mediator, and gallic acid (GA) was a more effective mediator than 1, 4-benzoquinone (BQ). The removal rate of IMI was increased by 1.8-fold in the presence of 100 μM of Mn 2+ compared with that of the system without Mn 2+ . The addition of oxalic acid and EDTA promoted the degradation of IMI, and the effect of oxalic acid was more pronounced at the later stage (day 5 and day 6); the optimal Fe 3+ /oxalate ratio was 1:3. Time-course experiments revealed the maximum removal rates of IMI were 97.37%, 82.0% and 73.52% at the initial IMI concentration of 10, 20, and 30 mg/L, respectively, in the presence of 100 μM Mn 2+, 100 μM Fe 3+ -300 μM of oxalate and 500 μM gallic acid. Under quinone redox cycling conditions, the good correlation between ·OH production rates and the enzymes activity was concluded, the quinines redox cycles promote enzyme activity, as well as the rate of ·OH production. Results from this study indicated the GA mediator-based system using P. chrysosporium offers a new method to advance the bio-oxidation process owing to its simple culture system, low-cost precursors, unique fungi, and degradation stability. Highlights: P. chrysosporium has the ability to drive advanced oxidation processes. Advanced bio-oxidation by P. chrysosporium increased its degradation ability. An appropriate amount of Mn 2+ is beneficial for IMI degradation. The substitution of Fe 3+ -EDTA by Fe 3+ -oxalate improve IMI degradation rate. The quinines redox cycles promote enzyme activity.